Flow cytometry for rapid characterisation of microbial community dynamics in waste stabilisation ponds. (1st February 2020) - Coggins, Liah X.; Larma, Irma; Hinchliffe, Amy; Props, Ruben; Ghadouani, Anas
Abstract: Algal and bacterial communities play a major role in the treatment performance and efficiency of waste stabilisation ponds (WSPs); however, the study of these WSP microbial communities has been challenging. Flow cytometry (FCM) has been used widely as a rapid, culture-independent method of characterising algae and/or bacteria in a range of freshwater and marine environments, and in conventional wastewater treatment processes, but its application to WSP wastewater has been underexplored. In this study, a method for the characterisation of both algal and bacterial microbial populations in WSP wastewater is presented and standardised, using cultures and field samples. We show that SYTO 16 dye is more effective than SYBR Green I for the concurrent detection of both algae and bacteria in samples. Through gating and phenotypic diversity analysis, the FCM results show both spatial and temporal shifts in pond microbial communities. The ability to rapidly determine the spatiotemporal shifts in pond populations is not only important for the improvement of pond operation and monitoring strategies, but also for the planning and management. Flow cytometry has the potential to become a diagnostic tool for ponds to assess treatment performance and determine the most optimal operating conditions. Graphical abstract: Image 1 Highlights: Flow cytometry can be used effectively to study microbial populations in WSPs. SYTO16 dye is most effective for concurrent detection of algae and bacteria. Results show spatial and temporal shifts in WSP microbial populations in pond.